Effect Of Deflector Angle Into Various Blades Configuration Of Single Stage Vertical Axis Savonius Hydro Turbine Performance - Gad Gunawan; Doddy Suanggana; Yun Tonce Kusuma Priyanto (Universitas Sultan Ageng Tirtayasa, 2020)
Electrical energy cannot be separated from human life. Today, the exploitation of energy leads to renewable energy. One of the renewable energy is water flow energy. The Savonius turbine is a type of water turbine which is suitable for low flow velocity. One method of increasing the performance of the Savonius Turbine is by using a deflector. This study aims to see the effect of using a deflector on the performance of the Savonius Turbine. The methodology used in this research is testing with variations in the number of turbine blades and deflector angle. The number of turbine blades used were two, three, and four blades, while the deflector angles used were 0°, 20°, 40°, 60°, and 80°. The result show that the using a deflector angle of 80° make turbine inlet flow is better. The best performance is obtained on the three blades Savonius Turbine and 80° deflector angle with power 0.154 Watt and coefficient of power 0.132.